DETERMINATION OF A RESTORATION PERIODS OF A FRAME INSULATION OF TM ED-118A BY RECOVERY VOLTAGE OBSERVATIONS - Laguta, V. V.; Коzік, Y. H. (Science and Transport Progress, 2020)
Purpose. The aim of the research is to improve the maintenance system of a traction motor (TM) ED-118A by predicting the life of a frame insulation and determining recovery moments while ensuring the lowest unit costs for performing a major repairs of a volume 1 (MjR-1) and permanent repair of a volume 3 (PR-3), taking into account the degree of recovery, using data on the insulation state by the recovery voltage method in the operation process. Methodology. The problem of determining the service life of the frame insulation and the corresponding moments of its recovery for the traction motor is formulated as an optimization problem. The criterion in the task is the minimum of the total unit costs for the implementation of PR-3 and MjR-1 during the period from the last MjR-2 (a major repairs of a volume 2) to the next MjR-2. Findings. The maximum value of the recovery voltage and the value of the integral estimate introduced are indicators characterizing the state of the frame insulation of the TM. As an indicator of the insulation state, an integral estimate is adopted, which is constructed by measuring the recovery voltage. Factories carrying out repairs of frame insulation have different quality of its restoration, which affects the unit cost of restoration and insulation service life. Originality. The optimization procedure takes into account the degree of insulation recovery when performing PR-3 and performing MjR-1. Modeling of the insulation service life and the recovery period of the PR-3 is based on measurements of the recovery voltage of the casing insulation, depending on the mileage. Practical value. The values of the integral indicator considered in the problem, changes in the recovery voltage of the casing insulation in the current measurement procedure, at which MT diagnostics are performed, can be used to predict the service life and simulate the moments of insulation recovery, as well as the maximum values of the recovery voltage in the current measurement procedure in accordance with mileage of a locomotive.